Usefulness of chest radiography in the context of the SARS-CoV-2 pandemic - Mayanga-Sausa, Silvia Lucía (2020)
In the current SARS-COV-2 pandemic, the choice of an imaging modality to aid diagnosis is based on the patient's clinical conditions, laboratory tests, and the availability of imaging equipment in health facilities. Tomography (CT) and chest radiography (CXR) are the most widely used imaging modalities; CXR, with less sensitivity than CT, is an accessible method, less expensive and less exposure to health personnel, its use is recommended in emergencies and in hospital services. The objective of the article is to guide decision-making to choose an imaging modality according to scenarios, taking into account its potential benefits and deepening in the description of the radiographic characteristics of suspected SARS-COV-2 infection that may serve in emergencies and we assess disease progression using a scoring system.